House of moons - Moody, Susan (Coronet, 1993)
Devastated by her brother's death in the Spanish Civil War, Mercedes vows to avenge him. When Tess Lovell's beloved guardian, Jonas, dies mysteriously on a trip to Spain, she returns to her mother's Spanish home town to discover the truth, and to face unresolved secrets of the past.